(untitled) (Research, Society and Development, 2019)
Artificial Intelligence is an area of computer research that is focused on developing mechanisms and devices to simulate human reasoning. Within this, an important subarea is the recognition of images. This article aims to describe the initial part of a research that aims to analyze and identify registered feelings of body expressions in videos of product reviews. Experimental tests have been planned to identify the best technique to solve the problem. Some forms of gesture identification through the use of neural networks were analyzed and tested.